Antibiotic Susceptibility Patterns of Recent Isolates of Corynebacterium diphtheriae - McLaughlin, Jane V. (1971)
A variety of factors which might affect zone sizes were studied with strains of Corynebacterium diphtheriae; a standard disc method for antimicrobial sensitivity testing was used. Moderate variations in inoculum size, inoculum preparation, and pH of Mueller Hinton agar (MHA) did not appreciably affect zone sizes. The addition of blood to MHA was necessary to insure the growth of all C. diphtheriae strains on all lots of MHA. Zone diameters on MHA with blood were consistently 4 to 9 mm smaller than on plain MHA; however, zone diameters were within the sensitive range for seven antibiotic discs used on both media. Minimal inhibitory concentration (MIC) values for penicillin, erythromycin, and rifampin were determined by a plate dilution method. The geographical source, toxigenicity, and type of the strains showed no significant correlation with MIC values or zone diameters for eight antibiotic discs. When MIC values were compared to obtainable blood levels, all of the strains appeared to be sensitive with MIC values of ≤ 0.5 μg/ml for penicillin and ≤ 0.01 μg/ml for erythromycin and rifampin. Strains from persons who failed to have C. diphtheriae eliminated by one course of treatment with penicillin or erythromycin were examined. The susceptibility of these strains did not vary significantly from that of the other strains studied.